2015
DOI: 10.3126/kumj.v11i4.12541
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Antibiotics Sensitivity in Childhood Urinary Tract Infection at Dhulikhel Hospital

Abstract: BackgroundUrinary Tract Infection implies presence of actively multiplying organisms in the urinary tract. Although it is infrequently associated with mortality, it is still a significant cause of morbidity. Early diagnosis is critical to preserve renal function of growing kidney. ObjectiveOur purpose was to determine the clinical, microbiologic profile and antibiotic sensitivity of such infections in pediatric Urinary Tract Infection (UTI) patients at Dhulikhel Hospital. MethodsA hospital based prospective de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
34
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 15 publications
17
34
5
Order By: Relevance
“…As reported in other studies, most UTIs are caused by uropathogenic Escherichia coli, followed by Klebsiella pneumonia, Enterococcus, Proteus, Acinetobacter, etc. 10,11 In our study, the most common organisms isolated were E. coli (67%), K. pneumonia (14.3%), Enterococcus (12.9%), Acinetobacter (4.3%), and Proteus (1.4%). These findings are consistent with findings by other studies by Mcloughlin TG.…”
mentioning
confidence: 58%
“…As reported in other studies, most UTIs are caused by uropathogenic Escherichia coli, followed by Klebsiella pneumonia, Enterococcus, Proteus, Acinetobacter, etc. 10,11 In our study, the most common organisms isolated were E. coli (67%), K. pneumonia (14.3%), Enterococcus (12.9%), Acinetobacter (4.3%), and Proteus (1.4%). These findings are consistent with findings by other studies by Mcloughlin TG.…”
mentioning
confidence: 58%
“…However, compared to reports from Nepal, we observed a considerable increase in resistance against penicillins, aminoglycosides, quinolones and ceftriaxone. 12 Lower rates of resistance among the paediatric isolates causing UTI have been documented in western countries. 31 In the present study Klebsiella isolates showed resistance against broad spectrum cephalosporin, macrolides and amoxicillin/clavulanic acid which is consistent with the previous data of other communitybased studies.…”
Section: Discussionmentioning
confidence: 99%
“…9 Most of the studies on paediatric urinary tract infections caused by multidrug resistant bacteria have been done in western world 10,11 , but these types of studies are scarce in South Asian region. 12 However, there are not much information on aetiology and resistance pattern of community acquired UTIs in Bangladesh. But drug resistance is spreading fast mainly due to overuse or underuse of antibiotics, incomplete medications and widespread practice of feeding livestock with low levels of antibiotics to promote growth.…”
Section: Introductionmentioning
confidence: 99%
“…Infection (UTI) implies the presence of actively multiplying organisms in the urinary tract (4,5) and it occurs in 3-5% of girls and 1% of boys during childhood, while it is more common in boys during the first year of life (6) . Every year about 250 million people worldwide are affected by UTIs.…”
Section: (1-3) Urinary Tractmentioning
confidence: 99%